Spark ignition engine modeling and control system design : a guide to model-in-the-loop hierarchical control methodology /: a guide to model-in-the-loop hierarchical control methodology. (2023) - Shamekhi, Amir-Mohammad; Shamekhi, Amir Hossein
No abstract available